A comparative analysis of financial affordability in Islamic home financing instruments in Malaysia - Md Zabri, Mohd Zaidi; Haron, Razali (Emerald Publishing Limited, 2019)
Purpose – This study aims to compare and contrast the financial affordability of Islamic home financing instruments such as bay’ bithaman ajil and musharakah mutanaqisah (MM) offered by various home financing institutions in Malaysia. Design/methodology/approach – Mathematical simulations were carried out in examining the financial affordability (or lack thereof) of various Islamic home financing by both Islamic commercial banks (ICB) and financial cooperatives (FC). Findings – This study has shown that MM by FC is a workable, more financially affordable option to potential homeowners. Unlike ICB, MM by FC uses rental rates as a benchmarking tool because of its inherent nature of flexibility. Research limitations/implications – MM by FC has the potential to reduce the cost of home acquisition (purchase affordability) and the amount of monthly installments (repayment affordability) of homeowners in Malaysia. Originality/value – This study shows the financial implication of unaffordable Islamic home financing instruments may have on the Malaysian households, which were derived from using official data from various government agencies.